Expression of glued laminated timber in long spans structures associated with its natural origin - Maciejko, Alicja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents an analysis of the possibilities of shaping long - span structures using the expressive force of glued laminated timber related to its natural origin. Changes that arose in the 20th century and at the beginning of the 21st century under the influence of new technological possibilities in the field of woodworking, as well as radical changes in the doctrine of environmental protection, also changed the position of timber as an innovative construction material.
Keywords: glued laminated timber; glulam; long-spans structures; large span constructions; structural design; conceptual design; symbolism of wood